2015
DOI: 10.1680/jgeen.13.00159
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of train-load-induced settlement in metro tunnels

Abstract: Based on a simplified mechanical model, the stress distribution pattern in subsoils around tunnels due to train movement is investigated. In this model, the effects of rails, connection bolts, ballast, lining and foundation are taken into account. The initial stress state and the dynamic stress state of the subsoils induced by train loading are obtained from a two-dimensional finite-element calculation. After combining the above results with the empirical equation proposed by Chai and Miura in 2002, the cumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…According to an investigation made by Ling et al [36], traffic loading at an intersection of the Shanghai outer ring road could result in a residual settlement of 50 mm. Wu et al's results [37] showed that the influential depth in the subsoil, in the soft Shanghai deposits, due to train vibration was around 4.5 m, and the maximum residual settlement from train vibration is about 20 mm.…”
Section: Additional Loadmentioning
confidence: 98%
“…According to an investigation made by Ling et al [36], traffic loading at an intersection of the Shanghai outer ring road could result in a residual settlement of 50 mm. Wu et al's results [37] showed that the influential depth in the subsoil, in the soft Shanghai deposits, due to train vibration was around 4.5 m, and the maximum residual settlement from train vibration is about 20 mm.…”
Section: Additional Loadmentioning
confidence: 98%
“…The long-term dynamic loading of the train will cause the deformation of the tunnel structure and the overall sinking to increase year by year, but the sinking amplitude is small [7]. Zhou et al combined the physical experiments and numerical simulations, they found that as the number of vibration loads increased, the growth rate of the cumulative deformation of the tunnel structure gradually decreased, and the cumulative deformation curve had a significant turning point [8].…”
Section: State Of the Artmentioning
confidence: 99%
“…It is important to predict and control over the SS induced by the tunneling construction, which may cause damage to adjacent structures. Empirical and analytical methods (Peck 1969;Lo et al 1984b;Lee 1989;Verruijt and Booker 1996;Loganathan and Poulos 1998;Hsieh and Ou 1998;Gonzales and Sagaseta 2001;Park 2005;Zhang et al 2009;Chen et al 2011), numerical methods (Karakus and Fowell 2003;Kasper and Meschke 2004; Hamid and Bahtiyar 2014; Ibrahim 2014; Shen and Xu 2011;Shen et al 2013Shen et al , 2014Shen et al , 2016Wu et al 2015aWu et al , 2015b, and artificial intelligence methods (Melis et al 2002;Suwansawat and Einstein 2006;Neaupane and Adhikari 2006;Pourtaghi and Lotfollahi 2012) have been widely used to estimate the SS due to tunneling. More recently Dindarloo and Siami-Irdemoosa (2015) have proposed the decision trees to predict SS.…”
Section: Researches On Ss Due To Tunnellingmentioning
confidence: 99%
“…However, the long-term deformation of the remoulded surrounding soil due to excavation disturbance and construction technologies are not taken into consideration in the analytical and empirical methods. Shen et al (2011Shen et al ( , 2013Shen et al ( , 2014Shen et al ( , 2016 and Wu et al (2015aWu et al ( , 2015b have proposed numerical evaluation methods of land subsidence induced by groundwater pumping, and then the numerical methods are widely used to predict the long-term settlement because of shield tunneling, nearby construction, groundwater infiltration, cyclic loading of trains and urbanisation. The model simulates the measured value fairly well in soft clay in Shanghai.…”
Section: R a F Tmentioning
confidence: 99%